$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}{\| #1 \|}$$ $$\newcommand{\inner}{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# 4.4: Inverse Functions

$$\newcommand{\vecs}{\overset { \rightharpoonup} {\mathbf{#1}} }$$

$$\newcommand{\vecd}{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$

An inverse function is a function that undoes another function: If an input $$x$$ into the function $$f$$ produces an output $$y$$, then putting $$y$$ into the inverse function $$g$$ produces the output $$x$$, and vice versa.

Definition: Inverse Functions

Let $$f(x)$$ be a 1-1 function then $$g(x)$$ is an inverse function of $$f(x)$$ if

$f(g(x)) = g(f(x)) = x.$

Example $$\PageIndex{1}$$

For

$f(x) = 2x - 1 \nonumber$

$f^{ -1}(x) = \dfrac{1}{2} x +\dfrac{1}{2} \nonumber$

since

$f(f^{ -1}(x) ) = 2[\dfrac{1}{2} x +\dfrac{1}{2}] - 1 = x \nonumber$

and

$f ^{-1}(f(x)) = \dfrac{1}{2} [2x - 1] + \dfrac{1}{2} = x. \nonumber$

## The Horizontal Line Test and Roll's Theorem

Note that if $$f(x)$$ is differentiable and the horizontal line test fails then

$f(a) = f(b)$

and Rolls theorem implies that there is a $$c$$ such that

$f '(c) = 0.$

A partial converse is also true:

Theorem (Roll's Theorem)

If $$f$$ is differentiable and $$f '(x)$$ is always non-negative (or always non-positive) then $$f(x)$$ has an inverse.

Example $$\PageIndex{2}$$

$f(x) = x^3 + x - 4 \nonumber$

has an inverse since

$f'(x) = 3x^2 + 1 \nonumber$

which is always positive.

## Continuity and Differentiability of the Inverse Function

Theorem (Continuity and Differentiability)

1. $$f$$ continuous implies that $$f^{ -1}$$ is continuous.
2. $$f$$ increasing implies that $$f^{ -1}$$ is increasing.
3. $$f$$ decreasing implies that $$f^{ -1}$$ is decreasing.
4. $$f$$ differentiable at $$c$$ and $$f '(c) \neq 0$$ implies that $$f^{ -1}$$ is differentiable at $$f (c)$$.
5. If $$g(x)$$ is the inverse of the differentiable $$f(x)$$ then

$g'(x) = \dfrac{1}{f '(g(x))}.$

if $$f '(g(x)) \neq 0$$.

Proof

Proof of (5)

Since

$f (g(x)) = x \nonumber$

we differentiate implicitly:

$\dfrac{d}{dx} f(g(x)) = \dfrac{d}{dx} x.\nonumber$

Using the chain rule

$y =f(u), u = g(x)\nonumber$

\begin{align*} \dfrac{dy}{x} &= \dfrac{dy}{dy} \dfrac{du}{dx} \nonumber \\[4pt] &= f '(u) g'(x) = f '(g(x)) g'(x). \end{align*}

So that

$f '(g(x)) g'(x) = 1. \nonumber$

Dividing, we get:

$g'(x) = \dfrac{1}{f'(g(x))}.\nonumber$

$$\square$$

Example $$\PageIndex{3}$$

For $$x > 0$$, let

$f(x) = x^2\nonumber$

and

$g(x) = \sqrt{x}\nonumber$

be its inverse, then

$g'(x) = \dfrac{1}{2\sqrt{x}}.\nonumber$

Note that

$\dfrac{d}{dx} \sqrt{x} = \dfrac{d}{dx} x^{\frac{1}{2}} = \dfrac{1}{2} x^{-\frac{1}{2}} = \dfrac{1}{2\sqrt{x}}.\nonumber$

Exercises

1. Let

$f(x) = x^3 + x - 4.\nonumber$

Find

$\dfrac{d}{dx} f^{-1}(-4). \nonumber$

2. Let

$f(x) =\int_2^x \dfrac{1}{1+x^3} dx\nonumber$

Find

$\dfrac{d}{dx} f^{-1}(0). \nonumber$